2011
DOI: 10.5194/acp-11-5079-2011
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric sulfur cycling in the southeastern Pacific – longitudinal distribution, vertical profile, and diel variability observed during VOCALS-REx

Abstract: Abstract. Dimethylsulfide (DMS) emitted from the ocean is a biogenic precursor gas for sulfur dioxide (SO 2 ) and non-sea-salt sulfate aerosols (SO 2− 4 ). During the VAMOSOcean-Cloud-Atmosphere-Land Study Regional Experiment (VOCALS-REx) in 2008, multiple instrumented platforms were deployed in the Southeastern Pacific (SEP) off the coast of Chile and Peru to study the linkage between aerosols and stratocumulus clouds. We present here observations from the NOAA Ship Ronald H. Brown and the NSF/NCAR C-130 airc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 64 publications
5
55
0
Order By: Relevance
“…Figure 5 shows schematically how each aerosol scheme responds to an increase in DMS flux. Both observations and modelling have shown that the dominant source of sulphate is through aqueous-phase oxidation in the presence of stratocumulus clouds (Andreae et al, 1999;O'Dowd et al, 1999;Yang et al, 2011;Woodhouse et al, 2013). The CLASSIC scheme, which does not simulate aerosol number and assumes a fixed modal distribution for sulphate aerosol, is only able to respond to an increase in sulphur by directly increasing the CCN number (label "a" in Fig.…”
Section: Response Of Ccn To Changes In Dmsmentioning
confidence: 99%
“…Figure 5 shows schematically how each aerosol scheme responds to an increase in DMS flux. Both observations and modelling have shown that the dominant source of sulphate is through aqueous-phase oxidation in the presence of stratocumulus clouds (Andreae et al, 1999;O'Dowd et al, 1999;Yang et al, 2011;Woodhouse et al, 2013). The CLASSIC scheme, which does not simulate aerosol number and assumes a fixed modal distribution for sulphate aerosol, is only able to respond to an increase in sulphur by directly increasing the CCN number (label "a" in Fig.…”
Section: Response Of Ccn To Changes In Dmsmentioning
confidence: 99%
“…Allen et al (2011) and Kleinman et al (2012) found that both carbon monoxide (a continental tracer) and sulfate aerosol mass also were higher in the boundary layer near shore than offshore. While sulfate aerosol can be produced from plankton-derived dimethylsulfide or DMS, Yang et al (2011a) showed that DMS actually tended to be lower near shore than offshore. These facts, together with the backtrajectories presented by Bretherton et al (2010), , and below, substantiate the hypothesis that the enhanced accumulation-mode particles near shore are derived from continental and not marine sources.…”
Section: Changes In Aerosol and Cloud Characteristics With Distance Fmentioning
confidence: 99%
“…Here we briefly describe the observations that are employed in this modeling study. Detailed descriptions of the instruments can be found elsewhere (e.g., Allen et al, 2011;Wood et al, 2011a;Yang et al, 2011).…”
Section: Observational Datamentioning
confidence: 99%